1990
DOI: 10.1063/1.346779
|View full text |Cite
|
Sign up to set email alerts
|

Growth-induced shallow acceptor defect and related luminescence effects in molecular beam epitaxial GaAs

Abstract: We report a study of a defect responsible for the ‘‘g’’ bound exciton line at 1.5112 eV that is frequently detected in photoluminescence spectra of GaAs grown by molecular beam epitaxy (MBE). A direct correlation has been observed between this line and a transition at 1.4946 eV, which is shown to result from a conduction band-to-acceptor recombination involving a shallow, unidentified acceptorlike defect that is labeled ‘‘A.’’ The activation energy of the defect is 24.8±0.2 meV, about 1.7 meV lower than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A low emission observed around 1.450 eV is linked to the two longitudinal optical phonon replicas (order 1) of (D 0 -A 0 ) and (e-A 0 ) transitions [50]. The emission centred at 1.513 eV mainly corresponds to neutral donors to valence band (D 0 -h), ionized donors to exciton transitions can also be detected close to this energy [49].…”
Section: Electrical Characterizationmentioning
confidence: 89%
See 1 more Smart Citation
“…A low emission observed around 1.450 eV is linked to the two longitudinal optical phonon replicas (order 1) of (D 0 -A 0 ) and (e-A 0 ) transitions [50]. The emission centred at 1.513 eV mainly corresponds to neutral donors to valence band (D 0 -h), ionized donors to exciton transitions can also be detected close to this energy [49].…”
Section: Electrical Characterizationmentioning
confidence: 89%
“…4. Same transitions are detected for all these samples; two dominant peaks are observed at 1.490 and 1.495 eV corresponding to both the transitions between neutral donor and neutral acceptor (D 0 -A 0 ) and that for band conduction and neutral acceptor (e-A 0 ) respectively [47][48][49][50]. A low emission observed around 1.450 eV is linked to the two longitudinal optical phonon replicas (order 1) of (D 0 -A 0 ) and (e-A 0 ) transitions [50].…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…[7][8][9] Wicks et al 7 have suggested that the origin of this defect is a group III vacancy which gets readily incorporated in GaAlAs layers. Szaferanek et al 10 have ruled out the possibility of a substitutional group II impurity to be the origin of this PL peak and have also observed that the presence of this peak quenches the acceptor bound exciton luminescence in GaAs layers. At a lower value of incident laser intensity, the PL intensity of the defect bound exciton peak at 1.825 eV is higher than that of the bound exciton peak at 1.845 eV.…”
mentioning
confidence: 99%